186 Validation of the HPV impact profile (HIP) in lebanese women with human papilloma virus or associated lesions. (13th November 2020) - Atallah, D; El Feghaly, C; El Feghaly, M; Moubarak, M; El Kassis, N; Abboud, S; Chahine, G
Abstract : Introduction: 'HPV impact profile' questionnaire, created by the team of Merck and coll. was one of the first and most specific tools evaluating the psychological impact of the most frequent gynecological lesions linked to HPV. This study aimed to translate the 'HIP' questionnaire into Arabic and to study its validity in a sample of Lebanese females. Methods: The HIP questionnaire was translated to Arabic following the scheme offered by Beaton et al. It was then administered to a sample of 118 Lebanese women infected with HPV or screened for HPV associated lesions, in parallel with the Hospital anxiety and depression scale (HADS) questionnaire. Results: The internal consistency of the HIP questionnaire was weak as alpha Cronbach coefficients of most of the domains were low. Therefore, the study of the composite matrix resulted in the improvement of the internal consistency after elimination of some items. The 'adapted domains' were created after inversing the scores of items with positive implications and similar studies were conducted on these domains. Then, the Composite Reliability (CR) and the Average Variance Extracted (AVE) of all the domains were analyzed as well as the Heterotrait-monotrait ratio of correlation. Finally, a statistically significant correlation was found between the total scores of the HIP and professional status and religion. Conclusion: The final version of the HIP presents good psychometric properties, allowing its use in clinical trials as well as in clinical practice in order to evaluate the quality of life in women with HPV.